Natural and induced blood dissemination of Toxoplasma gondii: experimental model in white mice and hamsters - Chinchilla, M (1993)
Blood inoculation in mice showed that Toxoplasma organisms circulate in blood after 1 h of oocyst infection. Parasites were detected up lo 15 days later and then dissapeared from the bloodstream concomitandy with cyst formation in the brain, probably due to antibody presence. Immunosuppression causedby cortisone acetate treatment induced Toxoplasma bloodstream invasion in chronically infected rnice and hamsters, causing death in some. Natural dissemination is discussed in relarion with congenital toxoplasmosis. Induced immunosuppressive effect is compared with that produced by natural diseases such as Hodgkin, lymphome, AIDS and others.